Assessment of Suicide Prevention on Nurses’ Knowledge at Psychiatric Teaching Hospitals in Baghdad City - Nada Abd Ali Mohammed Ali, Hassan A. Hussein (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Suicide is very sophisticated to be described in three brief words. Suicide attempts are also very uncommon and describing and foretelling them can be very hard. Theory, has the virtue in that it is an important tool in transforming information into knowledge. Material and Method: The study was carried out in Al-Rashad Psychiatric Teaching Hospital and Ibn Rushd Psychiatric Teaching Hospital in Baghdad City. A convenience sample was recruited from the aforementioned hospitals. Based on an effect size of 0.25, an alpha error probability of 0.05, a power of 0.80, number of groups = 2, and 3 measurements, the total sample size would be 72 who work in the previous mentioned setting were selected randomly for this study. The final sample size would be 72; 36 for the study group and 36 for the control group. The study instrument consists of participants’ sociodemographic sheet (age, gender, and marital status), employment profile (educational qualification, years of experience in nursing, years of experience in psychiatric units, and nurse-to-bed ratio. Results: The finding of study show that the participants in the study group is 34.33 ± 10.24; a half age 20-29-years (43%), followed by those who age 30-39-years (34.7%),and those who age 40-49-years (15.3%). Conclusion: The student researcher concluded that the nurses’ knowledge about suicide as a concept, nurses’ knowledge about suicide rate, nurses’ knowledge about factors contributing to suicide was weak.